Mathematical modelling of physically/geometrically non-linear micro-shells with account of coupling of temperature and deformation fields; Chaos, Solitons & Fractals; Vol. 104 - Awrejcewicz J. Jan; Krysko V. A. Vadim; Sopenko A. A. Aleksandr Anatoljevich; Zhigalov M. V. Maksim; Kirichenko A. V. Anastasiya Valerjevna; Krysko A. V. Anton Vadimovich (2017, 2017)
Title screen